Patient involvement in diabetes care: experiences in nine diabetes care groups - Lidwien Lemmens; Simone de Bruin; Jeroen Struijs; Mieke Rijken; Giel Nijpels; Caroline Baan (International Journal of Integrated Care, 2015)
Introduction: Despite the expected beneficial effects on quality of care, patient involvement in diabetes care groups, which deliver a bundled paid integrated care programme for diabetes type 2, seems to be limited. The aim of this study was to gain insight into levels and methods of patient involvement, into facilitators and barriers, and into the future preferences of care groups and patient representatives. Theory and methods: Semi-structured interviews were held with 10 representatives of care groups and 11 representatives of patient advocacy groups. An adapted version of Arnstein's ladder of citizen participation was used to define five levels of patient involvement. Results: Patient involvement in care groups was mostly limited to informing and consulting patients. Higher levels, i.e., advising, co-producing and decision-making, were less frequently observed. Care groups and patient representatives perceived largely the same barriers and facilitators and had similar preferences regarding future themes and design of patient involvement. Conclusion: Constructive collaboration between diabetes care groups and patient representatives to enhance patient involvement in the future seems viable. Several issues such as the lack of evidence for effectiveness of patient involvement, differences in viewpoints on the role and responsibilities of care groups and perceived barriers need to be addressed.